Navigating Through Unfamiliar Environments A Praxiological Approach to Pedestrian Wayfinding - Kazig, Rainer; Popp, Monika (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
The process how people manage to find their way has been discussed in the Anglo-Saxon literature already since the 1980s using the term wayfinding. However, as wayfindingresearch is mainly rooted within environmental psychology, it basically focuses on information processing. Thus, wayfinding research does not systematically take into account the influence of distinct settings and therefore it is only of limited use for urban planning. In this article we introduce a praxiological approach which highlights the embodiment and sensuality of wayfinding allowing to put a special focus on the relevance of environmental settings for wayfinding practices. We then present a method (commented walks), which captures wayfinding in situ and by doing so follows the requirements of our approach. The potentials of the praxiological approach for urban planning is finally demonstrated using two case studies.
Keywords: Pedestrian; Commented walks; Orientation; Praxiology; Wayfinding